Effective use of cloud computing in education: education as a service. (1st January 2013) - Gupta, Nakul; Goyal, Sushant
Cloud computing via its dynamic scalability is carving a new paradigm for virtual resources as well as services across the internet and beyond. It is likely to have a disruptive impact on most of the emerging sectors. Education is one such sector and is ripe for leveraging the offerings of cloud computing. Cloud computing is capable of delivering low cost, flexible, ubiquitous and on-demand educational services. In this paper, first the cloud computing infrastructure is reviewed. This is followed by the development of a comprehensive theory about online education and applicability of cloud computing in education. Post these preliminary discussions, models for utilising and adopting offerings of cloud computing in the field of education are proposed and future areas of research are identified.